Dissociation of Caloric and Video Head Impulse Tests in Patients With Delayed Endolymphatic Hydrops - Leng, Yangming; Liu, Bo (Frontiers in Neurology, 2020)
Delayed endolymphatic hydrops (DEH) represents a rare clinical entity characterized by intermittent vertigo attacks mimicking those of Ménière’s disease (MD) in a patient with a prior sensorineural hearing loss. Some vestibular tests have been employed in patients with DEH. These tests provide useful diagnostic information and facilitate clinical decision-making. Here, we retrospectively studied the features of video head impulse test (vHIT) and examined its relationship with caloric test used in DEH patients. Included in this study were 17 patients with ipsilateral DEH and 2 with contralateral DEH. Among them, 73.7% (14/19) showed abnormal caloric test response (76.5% in ipsilateral DEH and 50% in contralateral DEH). Meanwhile, only 15.8% (3/19) of patients yielded abnormal horizontal vHIT results (11.8% in ipsilateral DEH and 50% in contralateral DEH). Abnormal caloric response in the presence of a preserved vHIT was common in DEH patients, especially those with ipsilateral DEH. This dissociation might be a distinctive pattern of vestibular deficit in DEH.